2023
DOI: 10.1155/2023/7261784
|View full text |Cite
|
Sign up to set email alerts
|

Plant Growth-Promoting Rhizobacteria (PGPR) Reduce Adverse Effects of Salinity and Drought Stresses by Regulating Nutritional Profile of Barley

Sania Zaib,
Akmal Zubair,
Safdar Abbas
et al.

Abstract: With the growing emphasis on sustainable agriculture, food security, and environmental protection, the use of beneficial soil microbes is imperative, as the use of chemicals such as fertilizers, pesticides, and herbicides has resulted in food contamination, disease, weed resistance, and negative environmental consequences, which ultimately impacted human health. Climate change is a major factor and is of great concern for crop production. Abiotic stresses, including salt and drought stress, restrain the crop y… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 79 publications
(88 reference statements)
0
0
1
Order By: Relevance
“…Thus, more than half of the inoculated strains showed no ability to significantly increase the leaf chlorophyll content. These results were not expected and do not agree with those of Sania et al (2023), who showed that the use of PGPRs as an inoculant of barley (Hordeum vulgare L.) seeds in saline soils improved the leaf chlorophyll content. As groundnut is a legume species, its biological nitrogen fixation is mainly carried out in symbiotic association (Alexander et al, 2019), mainly with rhizobia.…”
Section: Discussioncontrasting
confidence: 83%
“…Thus, more than half of the inoculated strains showed no ability to significantly increase the leaf chlorophyll content. These results were not expected and do not agree with those of Sania et al (2023), who showed that the use of PGPRs as an inoculant of barley (Hordeum vulgare L.) seeds in saline soils improved the leaf chlorophyll content. As groundnut is a legume species, its biological nitrogen fixation is mainly carried out in symbiotic association (Alexander et al, 2019), mainly with rhizobia.…”
Section: Discussioncontrasting
confidence: 83%